An Analysis of Semiotic of Traditional Houses of Nias - Dakhi, Katarina Natalia; Sinambela, Erika; Sembiring, Rony Arahta (Universitas Pahlawan Tuanku Tambusai, 2024)
This research used a semiotic approach to analyze Nias' traditional houses, exploring the symbolism and meaning contained in the architecture and design elements. The traditional Nias house functions not only as a place to live but also as a representation of the cultural values, belief systems, and social identities of the Nias people. The research method included analysis of the signs and symbols on the house structure. The research results showed that every element of a Nias traditional house, from the basic structure to the decorative ornaments, has a deep symbolic meaning and reflects the harmonious relationship between humans, nature, and spirituality. These findings reinforce the importance of preserving Nias' traditional houses as part of Indonesia's rich and diverse cultural heritage.